Reservation Wages in Canadian Labour Markets - Hasan, Abrar; Gera, Surendra (Relations industrielles / Industrial Relations, 1982)
Job search theory has been offered in recent years as one explanation of unemployment. A key element of the theory requires that workers behave as if they operate on a reservation wage strategy. The authors verify this hypothesis.